The Microstructure and Mechanical Properties of Ferritic-Martensitic Steel EP-823 after High-Temperature Thermomechanical Treatment - Igor Litovchenko; Kseniya Almaeva; Nadezhda Polekhina; Sergey Akkuzin; Valeria Linnik; Evgeny Moskvichev; Vyacheslav Chernov; Maria Leontyeva-Smirnova (Metals, 2022)
The effect of high-temperature thermomechanical treatment (HTMT) with plastic deformation by rolling in austenitic region on the microstructure and mechanical properties of 12% chromium ferritic-martensitic steel EP-823 is investigated. The features of the grain and defect microstructure of steel are studied by Scanning Electron Microscopy with Electron Back-Scatter Diffraction (SEM EBSD) and Transmission Electron Microscopy (TEM). It is shown that HTMT leads to the formation of pancake structure with grains extended in the rolling direction and flattened in the rolling plane. The average sizes of martensitic packets and ferrite grains are approximately 1.5–2 times smaller compared to the corresponding values after traditional heat treatment (THT, which consists of normalization and tempering). The maximum grain size in the section parallel to the rolling plane increases up to more than 80 µm. HTMT leads to the formation of new sub-boundaries and a higher dislocation density. The fraction of low-angle misorientation boundaries reaches up to ≈68%, which exceeds the corresponding value after HTMT (55%). HTMT does not practically affect the carbide subsystem of steel. The mechanical properties are investigated by tensile tests in the temperature range 20–700 °C. It is shown that the values of the yield strength in this temperature range after HTMT increase relative to the corresponding values after THT. As a result of HTMT, the elongation decreases. A significant decrease is observed in the area of dynamic strain aging (DSA). The mechanisms of plastic deformation and strengthening of ferritic-martensitic steel under the high-temperature thermomechanical treatments are also discussed.